2018
DOI: 10.3847/1538-3881/aac883
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Haze Formation in the Atmospheres of Super-Earths and Mini-Neptunes

Abstract: UV radiation can induce photochemical processes in exoplanet atmospheres and produce haze particles. Recent observations suggest that haze and/or cloud layers could be present in the upper atmospheres of exoplanets. Haze particles play an important role in planetary atmospheres and may provide a source of organic material to the surface which may impact the origin or evolution of life. However, very little information is known about photochemical processes in cool, high-metallicity exoplanetary atmospheres. Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 42 publications
6
97
0
Order By: Relevance
“…At the temperature of WASP-6b, generation of hydrocarbons through photochemistry was initially thought to be inhibited (Liang et al 2004) and whilst sulphur photochemistry may play a role (Zahnle et al 2009), it primarily induces a scattering slope below 0.45 µm, whereas the observed slope of WASP-6b extends further into the optical. However, recent laboratory experiments have shown that hydrocarbons may form not just in cool exoplanet atmospheres (Hörst et al 2018;He et al 2018), but also in hot atmospheres beyond 1000 K with a sufficiently high [C/O] = 1 (Fleury et al 2019), a possibility our observations cannot definitively rule out. Additionally, the effects of wind-driven chemistry act to homogenise the atmospheres of tidally locked hot Jupiters such as WASP-6b and can lead to significant increases in the abundance of CH 4 compared to standard equilibrium models (Drummond et al 2018a,b).…”
Section: Wasp-6b In Contextmentioning
confidence: 74%
“…At the temperature of WASP-6b, generation of hydrocarbons through photochemistry was initially thought to be inhibited (Liang et al 2004) and whilst sulphur photochemistry may play a role (Zahnle et al 2009), it primarily induces a scattering slope below 0.45 µm, whereas the observed slope of WASP-6b extends further into the optical. However, recent laboratory experiments have shown that hydrocarbons may form not just in cool exoplanet atmospheres (Hörst et al 2018;He et al 2018), but also in hot atmospheres beyond 1000 K with a sufficiently high [C/O] = 1 (Fleury et al 2019), a possibility our observations cannot definitively rule out. Additionally, the effects of wind-driven chemistry act to homogenise the atmospheres of tidally locked hot Jupiters such as WASP-6b and can lead to significant increases in the abundance of CH 4 compared to standard equilibrium models (Drummond et al 2018a,b).…”
Section: Wasp-6b In Contextmentioning
confidence: 74%
“…Future telescopes, including the James Webb Space Telescope (JWST, scheduled to launch in 2021) and ground-based extremely large telescopes (planned to operate in the late 2020s), will characterize these atmospheres. However, observations and laboratory simulations indicate that condensate clouds and/or photochemical hazes could be ubiquitous in the atmospheres of exoplanets, affecting their observed spectra (Knutson et al 2014a(Knutson et al , 2014bKreidberg et al 2014;Dragomir et al 2015;Sing et al 2016;Lothringer et al 2018;He et al 2018a;Hörst et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experimental simulations have advanced our understanding of haze formation in planetary atmospheres in the Solar System, e.g., Titan (Cable et al 2012). Such simulations can also probe photochemistry in exoplanet atmospheres (He et al 2018a(He et al , 2018b(He et al , 2019Hörst et al 2018a;Berry et al 2019b;Fleury et al 2019;Moran et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The details of the setup varied due to the large variety of gases used for these experiments. Detailed description of the setup and experimental procedure can be found in our previous papers 13,14,16 . Figure 2 shows the initial gas mixtures for our experiments, calculated from the chemical equilibrium models 3 for 100×, 1000×, and 10000× solar metallicity over a range of temperatures (300, 400, and 600 K).…”
Section: Introductionmentioning
confidence: 99%